ASSESSING THE QUALITY OF CHILDCARE IN REGIONAL KINDERGARTENS - Li , Xin; Chen, Mei (Top Educational Review Journal (TERJ), 2023)
The quality of early childhood care and education is of paramount importance for the holistic development of children. This study examines the quality of the childcare and education process in kindergartens, with a focus on how various background variables of preschool teachers impact this aspect. Recently, the Ministry of Education in China issued guidelines emphasizing the importance of the quality of childcare and education in kindergartens. However, there is still a limited body of research in China that directly addresses the quality of the kindergarten process education. This research explores the link between background variables of preschool teachers and the quality of process childcare and education. The variables include age, gender, teaching experience, highest education level, the nature of the teaching unit, and the location of the kindergarten. By investigating these factors, the study aims to identify the key elements influencing the quality of process childcare and education in kindergartens. The findings of this study offer valuable insights into the improvement of preschool education quality and provide a framework for enhancing early childhood education in Hainan Province.